ANALISA WEBSITE W3SCHOOLS MENGGUNAKAN SYSTEM USABILITY SCALE - rasmila, rasmila; hanasti, fira; ellysza, santana (CV. Hawari, 2022)
Website is the main choice of learning web programming for a beginner, with the website can facilitate the learning process. The website used to learn programming tutorials is W3schools. W3schools is a web engineer data website, with instructional exercises and references connected with web improvement subjects like HTMLS, CSS, JavaScript, PHP, SQL, and Jquery. The webpage gives a reference guide that covers numerous ascept of web programming. This website there are many categories of tutorials to choose from but there are some users who do not really understand the feature contained in the W3schools website. Website usability according to Nielsen is learnbility, efficiency, memorability, errors, and satisfaction High convenience on site, for example, W3schools is capable draw in light of a legitimate concern for clients on the grounds that the utilization of the site is thought of as simple. The consequence of this paper are as quality investigation and ease of of W3schools of W3schools website based on the perception of various people who use W3schools website, so as to help W3schools website developers to improve the website that can provide satisfactions for its users.